Antibacterial Activity of Silver nanoparticles Against Pathogenic Bacterial Isolates from Diabetic Foot Patients - Ibraheem, Duaa R.; Hussein , Nehia N.; Sulaiman, Ghassan M. (Iraqi Journal of Science, 2023)
Diabetic foot is a catastrophic complication of diabetes. This study included isolation and identification of three types of bacteria that cause diabetic foot ulcers, fifty-five isolates of Staphylococcus aureus, thirty-five isolates of Acinetobacter baumannii, and thirty isolates of Serratia marcescens. These isolates were obtained from diabetic foot patients at different private clinics in and around Baghdad and Medical City Hospital. The proportion of male patients was greater than females, and it was noted that the age group (51-68 years) was more ages affected by diabetic foot. These isolates showed high resistance to most of the antibiotics used, Staphylococcus aureus was resistant to Penicillin, Tetracycline, and Ciprofloxacin in the percentage of 100 %, 65 %, and 26 %, respectively. Acinetobacter baumannii, showed high resistance to Penicillin, at a percentage of 80%, and Ciprofloxacin at 60%. Serratia marcescens was resistant to most antibiotics that were used in this study, Tetracycline, Penicillin, Cefotaxime, and Amoxicillin in the percent of (100, 95, 91, 88,70, and 64) %, respectively. The chemical reduction method was used in this study to synthesize silver nanoparticles. The characterization of silver nanoparticles was done by Field Emission Scanning Electron Microscope, and transmission electron microscope, which showed particle sizes of 24.56 to 66.2 nm, which proved that silver nanoparticles had nano size and spherical shape. The result of antibacterial activity of silver nanoparticles and silver nitrate against Staphylococcus aureus bacteria showed the highest effect of silver nitrate than other bacteria tested in this study, the diameter of the inhibition zone reached 15.66mm. Likewise for silver nanoparticles where the diameter of the inhibition zone of highest effect reached 29.33mm for Staphylococcus aureus bacteria. The test of silver nanoparticles’ ability to inhibit bacterial growth produced the greatest results for Staphylococcus aureus bacteria, which were inhibited after 60 minutes. Based on these research findings, silver nanoparticles have demonstrated their efficacy in this study against isolated bacteria from diabetic feet.